Counsellors’ perceived health promoting behaviours for enhancing physical well-being of clients - Helen Efeyadu, Uzoekwe; Grace Chinyere, Nnadi; Obianuju Blessing, Mokwelu; Edna Nkechi, Ofojebe,; Taiwo Abiodun, Ojo (International Journal of Scientific Research and Management (IJSRM), 2023)
This study adopts a descriptive survey design to seek for information, opinions and attitudes of the respondents and it is carried out in Anambra state of Nigeria. A total number of 143 counsellors who are willing to participate in the study are selected through accidental sampling technique.  The instrument ‘perceived counsellors’ health promoting behaviours for enhancing physical well-being of clients (PCSHPBSFEPWBOCS) developed by the researchers based on the information from the literature reviewed is used for data collections through direct approach distribution.  This instrument is validated by three experts. Test re-test was used to establish the reliability of the instrument and the reliability coefficient of 0.76 was obtained. The data collected are analyzed through the use of statistical weighted mean and ranking. Any mean score that is below 2.50 is accepted while any one below a mean score of 2.50 is rejected. The study revealed the following health promoting behaviours: engaging in daily exercise, taking healthy diet, minimizing hazards in the home and workplace, practicing effective hygiene, consumption of limited alcohol and tobacco, having adequate sleep and rest, little intake of salt, sugar and processed foods, adequate hydration, sunlight and fresh air having relaxed mind and maintaining a healthy body weight. The researchers recommend that Government should provide funds in support of the counsellors to educating and training people on promoting healthy behaviours that can enhance their physical well-being. Also, counsellors should increase the awareness on the adoption of these health promoting behaviours through the use of media and public announcements.